Three decades of protein phosphorylation and cancer: the identification and characterization of the src gene product - Erikson, Raymond (Henry Stewart Talks, 2010)
The avian sarcoma virus genome and its products, Cellular responses to the viral oncoprotein, Src, The search for the ASV src gene product, The RNA genome of avian sarcoma virus, Searching for Src a function, Impact of Src protein identification and characterization